Hierarchically structured macro-mesoporous carbon catalysts for saccharification of cellulose - Shaohua She; Luh Putu Pitrayani Sukma; Mingming Peng; Hisakazu Shirai; Yuto Suzuki; Kenji Kamiya; Eika W. Qian (Green Carbon, 2025)
Hierarchically structured macro-mesoporous carbon catalysts were synthesized using dual templates of poly(methyl methacrylate) (PMMA) and Pluronic-123 to enhance cellulose saccharification. Characterizations conducted through scanning electron microscopy (SEM), X-ray diffraction (XRD), N2 adsorption-desorption isotherms, Fourier transform infrared (FT-IR) spectroscopy, and titration techniques confirmed high surface areas and specific pore size distributions, with macropores ranging from 78.3 to 251 nm and mesopores around 2.43–6.23 nm. An optimal PMMA-to-Tetraethyl orthosilicate (TEOS) ratio of 1:1.6 facilitated the highest cellulose conversion rate of 59.3% and a glucose yield of 22.1%. Notably, the medium-sized macropore catalyst, MMCS60-M, outperformed its purely mesoporous counterpart, with conversion rates and glucose yields of 80.8% and 45.5%, respectively. These results suggest the importance of a tailored pore architecture to enhance the accessibility of acid sites and facilitate effective mass transport, which is beneficial for optimizing saccharification processes.